Bounded Stories. - Shanahan, Elizabeth A.; Raile, Eric D.; French, Kate A.; McEvoy, Jamie (Policy Studies Journal, 2018)
Narrative Policy Framework (NPF) and framing scholars share an interest in how the construction of policy arguments influences opinions and policy decisions. However, conceptual clarification is needed. This study advances the NPF by clarifying the meaning and function of frames and narrative, as well as their respective roles in creating policy realities. We explore sociological and psychological roots of framing scholarship and map these onto NPF's science of narratives philosophy, suggesting that narratives can reveal internally held cognitive schemas. We focus on issue categorization frames as boundaries for narrative construction. Within these bounds, narrative settings further focalize the audience by specifying where action toward a solution takes place. Based on 26 interviews with floodplain decision makers in Montana, we capture internally held cognitions through the assemblage of issue categorization frames and narrative elements. We find that settings can traverse issue categorization frames and policy solutions, with actions of characters that unfold within the setting being key. Similarly, we find that a single issue categorization frame can contain multiple different narratives and that individuals may simultaneously hold multiple different narratives internally. Overall, this study contributes to policy process research through establishment of connections among narratives, issue categorization frames, and cognitive schemas.